Spirit bound - Mead, Richelle (London : Penguin Books, 2013)
Rose Hathaway returns to St. Vladimir's in time for graduation, but while she looks forward to starting her life outside the academy, her heart longs for Dimitri; meanwhile, Dimitri begins to search for Rose with the intention of keeping her with him forever.
Young Adult.
Young Adult
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Supernatural -- Juvenile fiction; Vampires -- Juvenile fiction; High schools -- Fiction; Schools -- Fiction; Supernatural -- Fiction; Vampires -- Fiction; High schools -- Fiction; School stories; Supernatural -- Fiction; Vampires -- Fiction; Russia (Federation) -- Juvenile fiction; Siberia (Russia) -- Juvenile fiction; Russia (Federation) -- Fiction; Siberia (Russia) -- Fiction; Russia -- Fiction; Siberia (Russia) -- Fiction